Luteinizing hormone regulates the phosphorylation and localization of the mitochondrial effector dynamin‐related protein‐1 (DRP1) and steroidogenesis in the bovine corpus luteum. Issue 4 (20th February 2020) - Plewes, Michele R.; Hou, Xiaoying; Talbott, Heather A.; Zhang, Pan; Wood, Jennifer R.; Cupp, Andrea S.; Davis, John S.
Abstract: The corpus luteum is an endocrine gland that synthesizes and secretes progesterone. Luteinizing hormone (LH) activates protein kinase A (PKA) signaling in luteal cells, increasing delivery of substrate to mitochondria for progesterone production. Mitochondria maintain a highly regulated equilibrium between fusion and fission in order to sustain biological function. Dynamin‐related protein 1 (DRP1), is a key mediator of mitochondrial fission. The mechanism by which DRP1 is regulated in the ovary is largely unknown. We hypothesize that LH via PKA differentially regulates the phosphorylation of DRP1 on Ser616 and Ser637 in bovine luteal cells. In primary cultures of steroidogenic small luteal cells (SLCs), LH, and forskolin stimulated phosphorylation of DRP1 (Ser 637), and inhibited phosphorylation of DRP1 (Ser 616). Overexpression of a PKA inhibitor blocked the effects of LH and forskolin on DRP1 phosphorylation. In addition, LH decreased the association of DRP1 with the mitochondria. Genetic knockdown of the DRP1 mitochondria receptor, and a small molecule inhibitor of DRP1 increased basal and LH‐induced progesterone production. Studies with a general Dynamin inhibitor and siRNA knockdown of DRP1 showed that DRP1 is required for optimal LH‐induced progesterone biosynthesis. Taken together, the findings place DRP1 as an important target downstream of PKA in steroidogenic luteal cells.